DEVELOPMENT OF STUDENT WORKSHEETS (LKPD) BASED ON COOPERATIVE LEARNING TYPE STAD IN CLASS VII EARTH MATERIAL - Ayu Wahyuni; Nindha Ayu Berlianti (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2023)
The purpose of this development is to develop LKPD Student Team Achievement Divisions (STAD) Cooperative Learning-based worksheets on Class VII Earth Layer Material based on validity tests. The research method used is based on the ADDIE development procedure by describing the feasibility of the LKPD which was developed based on the Validity Test, the LKPD which was developed based on Cooperative Learning type Student Team Achievement Divisions (STAD) for the material on Layers of the Earth in Class VII. The results of the development carried out produced LKPD in accordance with the suggestions and input from the supervising lecturers and validators from material experts, media experts and science teachers. The results of the validator's assessment of Student Team Achievement Divisions (STAD) Cooperative Learning-based LKPDs show that the LKPD developed gets an average score of 4.52 for LKPD 1 in the very valid category and 4.39 in the very valid category for LKPD 2.